TRADISI UPACARA ADAT PERNIKAHAN SUKU KARO DI KABUPATEN KARO - Sri Wahyuni; Nurul Safitri; Waresqi Deardo Hutagalung; Paulus Sunatra Nduru; Devit Kristian Sinurat (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study discusses the traditional traditions carried out in the Karo tribal wedding ceremony in the Karo district. This study aims to find out how the arrangement of the Karo wedding ceremony has a lot of rules and rituals that must be carried out. In this study, using a descriptive method, the approach used is qualitative. Data was collected through literature studies, observations, books, and articles. The view of the Karo people regarding marriage customs is a very important question because, through marriage, love can be achieved and continuity of family lineage can be maintained. Apart from that, they will also have rights in all matters related to traditional rituals, and marriage will also bind two parties, namely the male family and the female family. Karo marriage has many rules, originating from the clan. All the rules for the wedding ceremony In the life of every tribal community, wherever there is always an order of social life that is respected and obeyed by the community group, members who disobey will be punished according to existing customs, one of which is marriage. Marriage is an important matter because the Karo tribe has orders or rules that must be followed according to Karo customary law, which is still adhered to today. Based on the explanation above, there are many traditional rituals of the Karo people that cannot be abandoned. And it can't be done haphazardly. The Karo people believe that marriage is very important because it is a bond between two parties, namely kalimbubu, anak beru, and others.Â Â Â